The efficient elimination of solid tumor cells by EGFR-specific and HER2-specific scFv-SNAP fusion proteins conjugated to benzylguanine-modified auristatin F. Issue 2 (28th October 2016) - Woitok, Mira; Klose, Diana; Niesen, Judith; Richter, Wolfgang; Abbas, Muhammad; Stein, Christoph; Fendel, Rolf; Bialon, Magdalena; Püttmann, Christiane; Fischer, Rainer; Barth, Stefan; Kolberg, Katharina
Highlights: Generation of site specific conjugated antibody drug conjugates with auristatin F. Use of SNAP-tag to couple auristatin to HER2-/EGFR-specific scFv-SNAP fusion proteins. Specific binding and internalization to HER2+ and EGFR+ tumor cell lines. Induction of cell cycle arrest and apoptosis demonstrated in vitro . Abstract: Antibody-drug conjugates (ADCs) combine the potency of cytotoxic drugs with the specificity of monoclonal antibodies (mAbs). Most ADCs are currently generated by the nonspecific conjugation of drug–linker reagents to certain amino acid residues in mAbs, resulting in a heterogeneous product. To overcome this limitation and prepare ADCs with a defined stoichiometry, we use SNAP-tag technology as an alternative conjugation strategy. This allows the site-specific conjugation of O(6)-benzylguanine (BG)-modified small molecules to SNAP-tag fusion proteins. To demonstrate the suitability of this system for the preparation of novel recombinant ADCs, here we conjugated SNAP-tagged single chain antibody fragments (scFvs) to a BG-modified version of auristatin F (AURIF). We used two scFv-SNAP fusion proteins targeting members of the epidermal growth factor receptor (EGFR) family that are frequently overexpressed in breast cancer. The conjugation of BG-AURIF to EGFR-specific 425(scFv)-SNAP and HER2-specific αHER2(scFv)-SNAP resulted in two potent recombinant ADCs that specifically killed breast cancer cell lines by inducing apoptosis when applied at nanomolar concentrations. These data confirm that SNAP-tag technology is a promising tool for the generation of novel recombinant ADCs.